Diffusion tensor imaging of brain changes in patients with chronic kidney disease before cognitive impairment with 3 T MRI device - Sherif Abdel Fattah Moustafa; Dina Abd Elnasser Rizk; Lamiaa Galal El Serougy; Mohamed El Said El Azab; Wessam Mustafa (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background Patients with chronic kidney disease (CKD) are at risk of a many of central nervous system complications such as stroke and cognitive impairment. Studies based on diffusion tensor imaging (DTI) confirmed that the integrity of white matter in CKD patients has changed and these alterations can be observed before tissue morphological changes occurring on conventional MRI. Early use of DTI in CKD patients can distinguish early individuals with normal cognitive system function and will develop cognitive impairment in later stages. Results As compared with controls, patients with CKD showed increased MD and decreased FA values in different brain regions with frontal, parietal regions and genu of corpus callosum more affected more than the occipital regions. For combined FA and MD in differentiating cases with CKD, there was statistically significant difference in both thalami, internal capsule, CC, cingulum, ILF and CST as p value < 0.05. Conclusions DTI with fiber tractography can present the mainstay of imaging in evaluating the white matter integrity in CKD patient has normal conventional MRI with better diagnostic accuracy in differentiation between healthy and altered white matters.